Paroster baylyi sp. n., P. ursulae sp. n. (Col. Dytiscidae, Hydroporinae) and the water beetle diversity of pan-gnammas on isolated granite outcrops in the Mallee of south-western Australia - Hendrich, Lars; Fery, Hans (Zootaxa, 2008)
Paroster baylyi sp. n. and P. ursulae sp. n. are described from south-western Australia, and compared with the similar P. michaelseni Régimbart, 1908. Their median lobes, parameres, gonocoxae, gonocoxosterna and habitus are illustrated, and details about their unique habitats and water beetle coenoses are given. The two new species are the first dytiscids to be known breeding solely in temporarily water filled rock-holes—so-called “pan-gnammas”—in the Mallee zone of south-western Australia. The total number of described species in the genus Paroster Sharp, 1882 is now 11. Eight aquatic Coleoptera of the families Dytiscidae and Hydrophilidae are recorded from 13 pan-gnammas on four granite outcrops in south-western Australia.